2022
DOI: 10.1039/d2ce00592a
|View full text |Cite
|
Sign up to set email alerts
|

Co-crystal synthesis of 2- and 4-mercaptopyridines with thiourea and its analogue, trithiocyanuric acid

Abstract: This article describes the synthesis of four new co-crystals obtained via cross-crystallisation of 2- and 4-mercaptopyridine with thiourea and trithiocyanuric acid, and examines their crystal structures. The resulting structures are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…It is also worth mentioning that the spontaneous in situ synthesis of mercaptopyridine sulfides from 3-and 4-mercaptopyridine has been reported recently (Wzgarda-Raj et al, 2021a,b), together with a proposed mechanism (Wzgarda-Raj et al, 2021a). In addition, it has been demonstrated that spontaneous in situ sulfide generation takes place under light conditions (Wzgarda-Raj et al, 2022). The three PTP(+) crystal structures deposited in the Cambridge Structural Database (CSD; Groom et al, 2016) are shown in Fig.…”
Section: Introductionmentioning
confidence: 80%
“…It is also worth mentioning that the spontaneous in situ synthesis of mercaptopyridine sulfides from 3-and 4-mercaptopyridine has been reported recently (Wzgarda-Raj et al, 2021a,b), together with a proposed mechanism (Wzgarda-Raj et al, 2021a). In addition, it has been demonstrated that spontaneous in situ sulfide generation takes place under light conditions (Wzgarda-Raj et al, 2022). The three PTP(+) crystal structures deposited in the Cambridge Structural Database (CSD; Groom et al, 2016) are shown in Fig.…”
Section: Introductionmentioning
confidence: 80%
“…This interaction connects the thiourea molecules. An analysis of the structural properties collected for such contacts found in thiourea crystal structures deposited at the Cambridge Structural Database (CSD; Groom et al, 2016) has been performed in a previous article (Wzgarda-Raj et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…Mercaptopyridine is a thiol compound with C 5 H 5 NS chemical formula that contains more than one hetero atom (i.e., S and N atoms) [ [28] , [29] , [30] ]. Mercaptopyridine derivatives are examples of organosulfur compounds that possess an important role in industry, pharmacology, and biology [ 31 ]. By dint of such hetero atoms, Mercaptopyridine derivatives gain the π-acidic nature, which imputes their promising role in coordination chemistry [ 32 ].…”
Section: Introductionmentioning
confidence: 99%